Model assessment of the water utilities transition to service quality criteria - Аleksandr А. Tskhai (Водное хозяйство России: проблемы, технологии, управление)
Th e paper analyzes consequences of the possible transition for Russian water supply and sewerage enterprises from quantitative efficiency criteria to qualitative ones. Such changes in goal-setting are now taking place in many developed and developing countries of the world.